AN ANALYSIS OF VOCABULARY LEARNING STRATEGIES AMONG EFL LEARNERS IN ENGLISH LANGUAGE ACQUISITION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes vocabulary learning strategies used by learners of English as a Foreign Language in the process of English language acquisition. The main aim of the study is to identify the most frequently used vocabulary learning strategies among EFL learners, evaluate their effectiveness, and reveal their impact on language acquisition. The article examines cognitive, metacognitive, memory-related, social, and compensatory vocabulary learning strategies from both theoretical and practical perspectives. The study employed a mixed-method approach using questionnaires, semi-structured interviews, and classroom observation. The findings indicate that learning words through context, repetition, translation, and the use of mobile applications are among the most common strategies used by learners. At the same time, learners who select strategies consciously and purposefully demonstrate better long-term retention and more active use of vocabulary in speech. The article concludes with pedagogical recommendations for the systematic teaching of vocabulary strategies in English classes.